162k views
3 votes
\begin{aligned} A.&&3(x+2)&=18 \\\\ B.&&3x+6&=18 \end{aligned} A. ​ 3(x+2) =18 B. 3x+6 =18

​ 1) How can we get Equation BBB from Equation AAA?

User SandyJoshi
by
5.0k points

1 Answer

6 votes


\huge\textbf{Use the distributive property.}


\begin{aligned}A.&&3(x+2)&=18\\ B.&&3x+6&=18 \end{aligned}

You can use the distributive property to get equation B from equation A.

The distributive property proves that
a(b+c)=ab+ac. Use this same logic on equation A, distributing
3 to
(x+2).


\begin{aligned}3(x+2)&=18\\3x+3(2)&=18\\3x+6&=18\end{aligned}

User Chris Sharp
by
5.9k points